Kemiskinan Struktural dan Pendapatan Petani Padi di Desa Cilapar Kecamatan Kaligondang Kabupaten Purbalingga - Giantama Adhy Prima; Lilis Siti Badriah; Suprapto Suprapto (EKO-REGIONAL, 2012)
This study, entitled "STRUCTURAL AND INCOME POVERTY IN THE VILLAGE OF RICE FARMERS CILAPAR SUB DISTRICT KALIGONDANG PURBALINGGA". The variables studied were the level of education, tenure and working hours to farmers’ income. The purpose of this study was to determine the effect of variable levels of education, tenure, and hours worked significantly to the farmers' income. Knowing the income of farmers in meeting their household needs. Know the description of the structural poverty of rice farmers.The research method used in this research is survey method. Methods used in sampling is stratified random sampling method. Number of respondents in this study is 74 respondents. The results of this study is the variable level of education, tenure status and working hours together influence against farmers' income. The median income of rice farmers have not been sufficient for his household as shown by the 68 respondents APC > 1 means consumption greater than income. Rice farmers living in poor conditions, as indicated by the value of revenues of more than 320kg of rice per capita rate.Increasing farmers' income if farmers further improve the working hours so that earned income is increasing, with increasing income of farmers, farmers may allocate income to other businesses open. Farmers should maximize their efforts in agriculture and trying to find another source of income. Farmers should be able to use the income as well as possible, or by setting aside part of their income for savings. Keywords:tenure, the structural poverty of rice farmers, poverty